ANALISIS BAHAN AJAR MATEMATIKA KELAS V SD DI KOTA MALANG - Nawang Sulistyani; Tyas Deviana (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2019)
The purpose of this paper is to explain the analysis of Mathematics teaching materials of Grade V Elementary Schools in Malang. The research method used is the type of qualitative research. The subject of this research is the fifth grade elementary school teacher in Malang. The type of data used is qualitative data obtained from the responses of teachers and students as users of teaching materials, as well as observational studies of the implementation of learning and documentation which includes the school curriculum, teaching material, and photos of learning activities. The research results that the teaching materials of Mathematics in Class V learning steps are accommodating for the achievement of learning objectives. The material is presented in an integrated and holistic manner according to the basic competencies that must be achieved. In general, the material is more on the discovery of concepts learned by students, not yet up to the application of concepts. Learning resources, facilities and learning experiences of students have not accommodated the local wisdom